ETIOLOGY, SYMPTOMS AND TREATMENT OF APERT SYNDROME, A CONGENITAL DISORDER: AN OVERVIEW - SATYANAND TYAGI,; SACHIN KUMAR,; MOHIT SINGLA, (International Journal of Pharma and Bio Sciences, 2010)
Apert syndrome is a genetic disorder characterized by the premature fusion of certain skull bones (craniosynostosis). This early fusion prevents the skull from growing normally and affects the shape of the head and face. In addition, a varied number of fingers and toes are fused together (syndactyly).Many of the characteristic facial features of Apert syndrome result from the premature fusion of the skull bones. The head is unable to grow normally, which leads to a sunken appearance in the middle of the face, bulging and wide-set eyes, a beaked nose, and an underdeveloped upper jaw leading to crowded teeth and other dental problems. Shallow eye sockets can cause vision problems. Early fusion of the skull bones also affects the development of the brain, which can disrupt intellectual development. Cognitive abilities in people with Apert syndrome range from normal to mild or moderate intellectual disability. Individuals with Apert syndrome have webbed or fused fingers and toes. The severity of the fusion varies; at a minimum, three digits on each hand and foot are fused together. In the most severe cases, all of the fingers and toes are fused. In the present article, we have concentrated on etiology, causes, symptoms, pathophysiology and treatment of Apert syndrome.